PENGARUH PUPUK ORGANIK HAYATI YANG MENGANDUNG MIKROBA BERMANFAAT TERHADAP PERTUMBUHAN DAN HASIL PANEN TANAMAN SEMANGKA SERTA SIFAT BIOKIMIA TANAHNYA PADA PERCOBAAN LAPANGAN DI MALINAU-KALIMANTAN TIMUR - Sarjiya Antonius; Dwi Agustiyani (The East Java Biological Society, 2011)
In field experiments during dry season 2010, the effects of biofertilization on growth of fruit yield Semangka (Citrullus lanatus) and of biochemical properties of soil were investigated. The experimental design was Randomly Block Design (RBD) with four treatments and five replications. The treatments were biofertilizer only; chemical fertilizer only; biofertilizer plus a half dose of chemical fertilizer, and control. The application of biofertilizer which was a mixture of Pseudomonas sp., Bacillus sp. and Streptomyces sp and chemical fertilizers (only 50% of the recommended dosage of NPK) increased vegetative growth (plant height, number of branches) compared to chemical fertilizer treatments only. An addition of biofertilizer with the chemical fertilizer also increased the biochemical properties as well as the yield of C. lanatus compared to other treatments. The possible role of biofertilizer on improving soil enzymatic activities, vegetative growths and yield will be discussed more detail in the paper.